Family Functioning and Emotional Behaviour Problems: Mediating Role of Cognitive Emotional Regulation Strategies Among Slum Dwelling Adolescents - Qayyum, Hira; Khan, Saira (Annals of Human and Social Sciences, 2025)
The study examined the mediating role of adaptive and maladaptive cognitive emotional regulation strategies between family functioning and emotional behaviour problems among slum dwelling adolescents. This group faces significant challenges that impact their mental health and well-being. Teaching effective coping mechanisms are crucial for promoting mental health. A quantitative approach was employed, using purposive sampling to target 400 adolescents (214 boys, 186 girls) aged 10-20 years (M = 15.36; SD = 3.06). The sample was taken from Islamabad, Mandra Gujar Khan and Sohawa. The data was analysed using Process Marco by Hyes. The result of mediation analyses confirmed that the adaptive and maladaptive strategies partially mediated the link between family functioning and externalizing and internalizing behaviour problems. Based on the results, prevention and intervention programs can be introduced to strengthen family functioning and save the slum dweller from developing emotional behaviour problems.